2019
DOI: 10.5194/wes-2019-68
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The impact of a forest parametrization on coupled WRF-CFD simulations during the passage of a cold front over the WINSENT test-site

Abstract: Abstract. The Weather Research and Forecasting (WRF) Model has been coupled with a URANS Model to simulate the passage of a cold front over the WINSENT site, a wind energy test-site under development. It is located on a hill near a steep, forested terrain edge. A high spatial resolution is necessary to simulate the flow over this complex site accurately for which reason the WRF model is run at high resolution in LES mode coupled to a URANS model with an even higher resolution. A forest parametrization is imple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…In recent years, a large amount of wind engineering and research on wind modeling has been conducted by using the atmospheric and CFD coupled system as computer hardware and computational resources are rapidly advancing. Reference [23] used WRF-LES to drive Open-Source Field Operation and Manipulation (OpenFOAM) simulations with an Unsteady Reynolds-Averaged Navier-Stokes (URANS) turbulence model to simulate the passage of a cold front over a windenergy test site over a hill. e evaluation of wind speed against measurements from tower and UAS data showed that this coupling was able to simulate reasonably various flow micro features.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a large amount of wind engineering and research on wind modeling has been conducted by using the atmospheric and CFD coupled system as computer hardware and computational resources are rapidly advancing. Reference [23] used WRF-LES to drive Open-Source Field Operation and Manipulation (OpenFOAM) simulations with an Unsteady Reynolds-Averaged Navier-Stokes (URANS) turbulence model to simulate the passage of a cold front over a windenergy test site over a hill. e evaluation of wind speed against measurements from tower and UAS data showed that this coupling was able to simulate reasonably various flow micro features.…”
Section: Introductionmentioning
confidence: 99%